Temporal Changes in Long‐Term Outcomes of Venous Thromboembolism From the Warfarin Era to the Direct Oral Anticoagulant Era - Kazuhisa Kaneda; Yugo Yamashita; Takeshi Morimoto; Ryuki Chatani; Yuji Nishimoto; Nobutaka Ikeda; Yohei Kobayashi; Satoshi Ikeda; Kitae Kim; Moriaki Inoko; Toru Takase; Shuhei Tsuji; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background There have been limited data on the changes in clinical outcomes after the introduction of direct oral anticoagulants (DOACs) for venous thromboembolism (VTE) in real clinical practice. We evaluated the changes in management strategies and long‐term outcomes from the warfarin era to the DOAC era. Methods and Results We compared the 2 series of multicenter COMMAND VTE (Contemporary Management and Outcomes in Patients With Venous Thromboembolism) registries in Japan enrolling consecutive patients with acute symptomatic VTE: Registry 1: 3027 patients in the warfarin era (2010–2014) and Registry 2: 5197 patients in the DOAC era (2015–2020). The prevalence of DOAC use increased more in Registry 2 than in the Registry 1 (Registry 1: 2.6% versus Registry 2: 79%, P<0.001). The cumulative 5‐year incidence of recurrent VTE was significantly lower in Registry 2 than in Registry 1 (10.5% versus 9.5%, P=0.02), and the risk reduction of recurrent VTE in Registry 2 remained significant even after adjusting the confounders (hazard ratio [HR], 0.78 [95% CI, 0.65–0.93]; P=0.005). The cumulative 5‐year incidence of major bleeding was not significantly different between the 2 registries (12.1% versus 13.7%, P=0.26), and the risk of major bleeding between the 2 registries was not significantly different even after adjusting the confounders (HR, 1.04 [95% CI, 0.89–1.21]; P=0.63). Conclusions Along with the shift from warfarin to DOACs, there was a lower risk of recurrent VTE in the DOAC era than in the warfarin era, whereas there was no apparent change in the risk of major bleeding, which might still be an unmet need even in the DOAC era.